ANALISIS KELAYAKAN BISNIS PASAR WISATA MINGGON JATINAN KABUPATEN BATANG - Mahirdini, Wardah (Universitas Bunda Mulia, 2023)
Minggon Jatinan is a traditional market development project that aims to improve the local economy in Batang Regency. The purpose of this research is to conduct a business feasibility study for the Minggon Jatinan Market development project. This research was conducted by analyzing the key aspects that influence the success of the project, including market analysis, financial analysis, technical analysis, and management analysis. The research method used is a qualitative approach. Primary data was collected through direct surveys of potential traders and potential consumers of Pasar Minggon Jatinan, as well as interviews with related parties such as the local government and land owners. Secondary data was obtained through literature studies and related information sources. The results of the market analysis show that there is a sizeable market potential for Pasar Minggon Jatinan, with high interest from the local community and the surrounding area. Financial analysis shows that this project has a profitable profit potential, with a positive return on investment in the long term. The technical analysis involves evaluating the location, infrastructure, facilities and operational needs of Pasar Minggon Jatinan. In this case, it was found that the selected location had good accessibility and adequate facilities to support market operations. Management analysis involves assessing market management, including organizational structure, business planning, and marketing strategy. The results of the analysis show that with effective management and adequate support from the local government, Pasar Minggon Jatinan has the potential to become a successful and sustainable business. Based on the findings from this business feasibility analysis, it is suggested that the Minggon Jatinan Market development project can be continued. However, proper strategic steps need to be taken, such as effective marketing, selection of quality traders, and maintenance of good market facilities and cleanliness.